Penyuluhan tentang penyakit paru obstruktif kronik di Poli Paru RSUD Provinsi NTB - Indana Eva Ajmala; Hamsu Kadriyan; Rina Lestari; Arfi Syamsun; Eka Arie Yuliyani (INDRA: Jurnal Pengabdian kepada Masyarakat, 2020)
Chronic Obstructive Pulmonary Disease (COPD) is still a particular concern because it has a high prevalence, morbidity and mortality. COPD is not yet popular in the community. The major risk factor is smoking. There are many other risk factors that must be avoided so that they are not exposed to COPD or their disease does not get worse. The purpose of this counseling is to increase the knowledge of patients and their families about COPD so that changes in thinking and behavior about the disease occur.This counseling was carried out at the Pulmonary Outpatient Clinic, General Hospital of West Nusa Tenggara Province, by students of Medical Faculty Mataram University. There were a presentation of material about COPD, distribution of brochures and discussions. This counseling activity was held on June 26, 2019 and was attended by 38 people, consisting of patients and their families. The participants seemed very enthusiastic to follow the counseling to the end and asked a few questions. Counseling participants have additional knowledge about COPD.